Precision oncology through next generation sequencing in hepatocellular carcinoma - Sayali Shinde; Carola Maria Bigogno; Ana Simmons; Nikita Kathuria; Aruni Ghose; Vedika Apte; Patricia Lapitan; Shania Makker; Aydin Caglayan; Stergios Boussios (Heliyon)
Hepatocellular carcinoma (HCC) is a primary liver cancer that originates from underlying inflammation, often associated with Hepatitis B virus (HBV) or Hepatitis C virus (HCV) infections. Despite the availability of treatments, there are high rates of tumour relapse due to the development of drug resistance in infected cells. Next-Generation Sequencing (NGS) plays a crucial role in overcoming this issue by sequencing both viral and host genomes to identify mutations and genetic heterogeneity. The knowledge gained from sequencing is then utilised to develop countermeasures against these mutants through different combination therapies. Advances in NGS have led to sequencing with higher accuracy and throughput, thereby enabling personalized and effective treatments. The purpose of this article is to highlight how NGS has contributed to precision medicine in HCC and the possible integration of artificial intelligence (AI) to bolster the advancement.